2020
DOI: 10.1177/1559325820917829
|View full text |Cite
|
Sign up to set email alerts
|

Small Nucleolar RNA, C/D Box 16 (SNORD16) Acts as a Potential Prognostic Biomarker in Colon Cancer

Abstract: Colon cancer (CC) is considered one of the most common and lethal malignancies occurring both in male and female. Its widespread prevalence demonstrates the need for novel diagnostic and prognostic biomarkers for CC. Emerging evidence has shown that small nucleolar RNAs play critical roles in tumor development. In this study, we investigated the expression profile and functions of SNORD16 in CC. Our data showed that SNORD16, rather than its host gene (RPL4), was upregulated in CC cell lines. Compared to matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…15 In colon cancer, SNORD16 promotes tumorigenesis, and SNORD16 knockdown restrains the proliferated, migrated, and invaded ability of colon cancer cells and promotes apoptosis. 16 SNORD12B is formed from the splicing intron of the long noncoding RNA ZFAS1. SNORD12B expression is upregulated in colon cancer and is correlated with its metastasis.…”
Section: Snornas As Novel Molecular Targets For Cancer Treatmentmentioning
confidence: 99%
“…15 In colon cancer, SNORD16 promotes tumorigenesis, and SNORD16 knockdown restrains the proliferated, migrated, and invaded ability of colon cancer cells and promotes apoptosis. 16 SNORD12B is formed from the splicing intron of the long noncoding RNA ZFAS1. SNORD12B expression is upregulated in colon cancer and is correlated with its metastasis.…”
Section: Snornas As Novel Molecular Targets For Cancer Treatmentmentioning
confidence: 99%
“…The human nucleolar enzyme NSUN5 catalyzes the C 5 methylation of cytosine residue C 3782 of the 28S rRNA (18S-m 5 C3782) and is upregulated in CRC and associated with disease progression [153]. The C/D-Box small nucleolar RNA 16 (SNORD16) guides fibrillarin (FBL) to methylate the 2 O-ribose on the 18S-Am484 site and constitutes a molecular marker of CRC and a driver of colorectal tumorigenesis [154]. The ribosome biogenesis protein TSR3 induces the 1-methyl-3α-amino-α-carboxyl-propyl pseudouridine (m 1 acp 3 Ψ) modification on uridine U1248 of the 18S rRNA and is overexpressed in CRC and associated with colorectal tumorigenesis [155].…”
Section: Regulation Of Ribosome Biogenesis By Ribosomal Proteins In Crcmentioning
confidence: 99%
“…In human Hela cells, SNORD16 is the snoRNA which directly interacts with the 18S rRNA and guides FBL to methylate the 2 O-ribose on the 18S-Am484 site [167]. It was recently shown that SNORD16 is a molecular marker of human CRC and a driver of colorectal tumorigenesis [154]. SNORD16 overexpression is significantly correlated with age, cancer cell invasion, patient history of colon polyps, and is associated with a poor patient overall survival [154].…”
Section: Chemical Modifications Of Rrna In Crcmentioning
confidence: 99%
See 2 more Smart Citations